TRANSFORMATIONAL LEADERSHIP APPLIED BY RIDWAN KAMIL AS REGIONAL GOVERNMENT - Novitasari, Nita; Choiriyah , Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines the implementation of transformational leadership by Ridwan Kamil within the framework of local government, focusing on his leadership during his tenure as Mayor of Bandung and Governor of West Java. Specifically, it explores three dimensions of transformational leadership proposed by Bass (1990): inspirational motivation, intellectual stimulation, and individualized consideration. Method: The study employs a qualitative literature review with a descriptive analytical approach, utilizing secondary data from academic journals, books, research reports, and official documents related to regional leadership. Results: The findings reveal that Ridwan Kamil effectively applied transformational leadership principles through a creative and inclusive urban development vision, digital innovation in public services, and personalized engagement with the community. Nevertheless, several challenges persisted, particularly bureaucratic rigidity, infrastructure constraints, and demographic diversity in West Java. Novelty: This study contributes to the literature by demonstrating that transformational leadership significantly enhances public participation, reinforces leadership legitimacy, and stimulates innovation in local governance, thereby enriching Bass’s (1990) theoretical model and offering practical insights for regional leadership practices in Indonesia.